Pengaruh Performa Quay Container Crane dan Penerapan System Single Cycle dan Dual Cycle Terhadap Bongkar Muat Peti Kemas di KSO Peti Kemas Koja Jakarta - Ridwan; Aji Luhur; Muhammad Elnath G (Jurnal Maritim Polimarin, 2023)
Since 2012 Koja Jakarta Container Terminal has a target of unloading and loading 1 million containers. To get the desired target, KSO Koja Container Terminal immediately took quick steps by upgrading and adding several tools to support performance so that it could be more optimal in carrying out loading and unloading activities such as upgrading several CCs from Post Panamax grade to Super Post Panamax. Along with the many containers that are unloaded or loaded at TPK KOJA, and the market that competes between container terminals with each other. The management of Koja must increase the target size of unloading and loading containers by quay container crane (QCC) or what we often call Box Crane per Hours (BCH), but on the other hand with the demands of TPK KOJA management that unloading and loading 1 million containers, many tools in the field and at the dock are forced to work hours with maintenance that has not been scheduled properly resulting in congestion of loading and unloading equipment. The type of research used in this study is qualitative descriptive analysis, qualitative descriptive research is aimed at describing and describing existing phenomena, both natural and human engineering, which pay more attention to the characteristics, quality, relationships between activities. In addition, descriptive research does not provide treatment, manipulation or alteration of the variables studied, but describes a condition as it is. So the results of the Quay container crane performance research at TPK Koja from the author's observation, in the process of container loading and unloading activities at TPK Koja still found inhibiting factors. The effect of the Dual Cycle Operation system in loading and unloading at TPK KOJA cannot be determined the box crane unit per hour produced, because in this case the management of TPK KOJA is still in the trial stage of the system.